Investigation of the possible protective effect of N-Acetylcysteine (NAC) against Irinotecan (CPT-11)-Induced toxicity in rats - BÖLÜKBAŞI, FURKAN (My University, 2022)
Irinotecan (CPT-11) is a chemotherapeutic agent involved in the treatment regimens for several malignancies such as colorectal cancer. N-acetylcysteine (NAC) is a strong antioxidant and anti-inflammatory agent used in the treatment of several diseases related to oxidative stress and inflammation. This study aimed at investigating whether NAC provides protection against hepatorenal and gastrointestinal tissue damage induced by CPT-11. Thirty-two Wistar albino rats were divided into four groups as control, NAC, CPT-11, and CPT-11+NAC. Following the experimental period, blood, and tissue samples (liver, kidney, stomach, and small intestine) were collected, and biochemical indicators, together with pro-inflammatory cytokines (TNF-α and IL-1β), matrix metalloproteinases (MMPs), malondialdehyde (MDA), glutathione peroxidase (GPx) and superoxide dismutase (SOD) levels were evaluated. Both the biochemical indicators and the pro-inflammatory cytokines, MMP, and MDA levels increased in animals treated with CPT-11, while SOD and GPx activities decreased. Histopathological evaluation revealed structural damage in all examined tissues. With NAC administration, significant improvements were observed, both biochemically and histologically. In conclusion, the results of the present study suggest that NAC treatment together with CPT-11 may have a beneficial effect on reducing CPT-11 toxicity in rats, by modulating inflammation and the oxidant–antioxidant balance. These results strongly promote further investigative studies.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE; cancer chemotherapy; irinotecan; N-acetylcysteine; matrix metalloproteinase; proinflammatory cytokines; malondialdehyd